Peningkatan Organizational Citizenship Behavior (OCB) Melalui Penguatan Kepemimpinan Karismatik dan Kecerdasan Spiritual - Wawan Kurniawan; Eka Suhardi; Hari Muharam (Universitas Pakuan, 2022)
Improving Organizational Citizenship Behavior (OCB) through Strengthening Charismatic Leadership and Spiritual IntelligenceThe purpose of this study was to find the ways to improve teachers organizational citizenship behavior (OCB) through analysis on the strength of the relationship between charismatic leadership, spiritual intelligence, and teacher OCB, either individually or together. This research was conducted at private Islamic elementary schools in East Telukjambe sub-district, Karawang regency, involving 104 teachers of permanent foundation teachers. The research method used is descriptive quantitative with correlation analysis. The instruments used for data collection consisted of teacher OCB, charismatic leadership, and teacher spiritual intelligence. The result of the study; 1) there was a positive relationship between Charismatic Leadership and OCB Teachers (ry1 = 0.696, 0.01), 2) there was a positive relationship between teacher spiritual intelligence and OCB teachers (ry2 = 0.710, 0.01), 3) there was a positive and very significant relationship between Charismatic Leadership and Spiritual Intelligence together with OCB (ry12 = 0.775, 0.01). The conclusion is the OCB can be increased by strengthening charismatic leadership and spiritual intelligence.